Analisis Reduplikasi pada Cerita Pendek “Buhaya Kuning” Karya Rahmiyati - Zahra Anisa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study discusses reduplication as one of the important morphological processes in the Indonesian language. Reduplication plays a role in the formation of words and serves to express various grammatical meanings, such as plural, frequency, intensity, and continuity of an event. The purpose of this study is to describe the types of reduplication and the classes of words produced through this process. The research data is in the form of duplicated words, including materials, people, years, destruction, many times, and shouting. The method used is qualitative descriptive with analysis techniques in the form of classification based on the type of reduplication, namely intact reduplication, partial reduplication, reduplication with adjustment, and altered reduplication of sounds. The results of the study show that reduplication in Indonesian can form various classes of words, such as nouns, verbs, adjectives, and adverbs, with different grammatical functions according to the context of their use. These findings confirm that reduplication not only serves as a repetition of forms, but also has a significant semantic and syntactic role in the structure of language. This research is expected to make a theoretical contribution to the study of Indonesian morphology and become a reference for future linguistic research, especially in understanding the dynamics of word formation and meanings produced through the process of reduplication.